POPULASI DAN PERILAKU KERA EKOR PANJANG (Macaca fascicularis) DI DESA PANCASARI SUKASADA BULELENG BALI - Mahayuni, Ni Putu Kiki; Watiniasih, Ni Luh; Yusup, Deny Suhernawan (SIMBIOSIS, 2018)
ABSTRACT             Long-tailed macaque ( Macacafascicularis ) has its name as the length of its tail as long as its body. One of their habitats is located in Pancasari Village, Sukasada, Buleleng, Bali. Its current number and their daily activity has not been scientifically studied. This research, aimed to determine the number of individuals in its age groups, and the in daily activity as. The population was calculateemploying census method and was distinguish accordingly to different age group (a) adult, (b) juveniles and (d) infant, ceusused three times that inthe morning at 09.00-10.00, during the day at 11.00-12.00and in the afternoon at 13.00-14.00. Daily activities of this macaque were recorded with animal focal scan sampling method , twice in a day, in the morning at 09.00-11.00 and in the afternoon at 14.00-16.00 for 7 days. The population of long-tailed macaques in this are is 252, consisting of 96 adult male, 85 adult females, 44 juveniles and 27 infants. The long tail macaques at Pancasariuse most of their time for moving (30%), followed by eating (27%)and resting (22%). Only 2% of their daily time was used for aggressive and mating. Keywords: M acaca fascicularis, population, daily activities